A Critical Study of People's Sovereignty Post-Amendment of the 1945 Constitution in Strengthening the Presidential System - Aurelita Gissella; Saiful Anwar (Letiges, 2026)
This study critically examines the concept of people's sovereignty following the amendments to the 1945 Constitution of Indonesia, with a particular focus on its role in strengthening the presidential system. The research aims to identify key issues related to the implementation of people's sovereignty after the amendments, analyze the extent to which these changes have contributed to the consolidation of the presidential system, and assess the effectiveness and challenges of the new constitutional framework. Using a normative juridical approach combined with a critical analysis of legal documents and relevant literature, the study finds that the constitutional amendments significantly enhanced the principle of direct democracy and clarified the separation of powers. However, several challenges remain in ensuring the optimal realization of people's sovereignty within the presidential system, particularly regarding checks and balances and institutional practices.